Perancangan Website Pendataan Troubleshooting pada Biro Teknologi Informasi Menggunakan Laravel Studi Kasus Universitas Mercu Buana: Website Design for Troubleshooting Data Collection at the Information Technology Bureau Using Laravel: A Case Study at Mercu Buana University - Muhammad Ghufroon Roffif; Tamatjita, Elizabeth Nurmiyati (Information Technology and Science (ITScience), 2026)
Troubleshooting records at the Information Technology Bureau of Mercu Buana University are still maintained manually, resulting in difficulties tracking reports, data duplication, and delays in handling IT disruptions. These conditions reduce service effectiveness and make it difficult to conduct comprehensive performance evaluations. Therefore, this study aims to design and implement a web-based troubleshooting recording information system capable of managing disruption reports in a structured manner, monitoring repair status in real time, and providing historical data for evaluating IT service performance. The system development method used in this study is the System Development Life Cycle (SDLC), which includes the stages of needs analysis, system design, implementation, and testing. The system was developed using the Laravel framework with a MySQL database to ensure centralised, secure, and integrated data management. System testing was conducted using the black-box testing method to ensure that all functions met user requirements. The test results show that the developed system can speed up the report recording process by up to 45%, increase transparency into the status of disruption handling, and facilitate data-driven decision-making. In addition, the implementation of this system supports the incident management process in accordance with the Information Technology Infrastructure Library (ITIL) principles. It contributes to increasing the efficiency, accountability, and quality of information technology services within the Mercu Buana University environment.